2022
DOI: 10.1055/s-0042-1755441
|View full text |Cite
|
Sign up to set email alerts
|

Doctors' Perceptions of Rare Bone Disorders and X-Linked Hypophosphatemia: A Survey from Africa and the Middle East

Abstract: Objectives To assess the perceptions of genetic and metabolic bone disorders with a focus on X-linked hypophosphatemia (XLH) in the Middle East and Africa. Methods An online survey of a convenience sample of physicians from relevant disciplines. The questions covered respondents' profiles, awareness of rare bone diseases, and XLH's burden, symptoms, and management. Results A total of 139 respondents were included in the analysis. Responses came from the Arabian Gulf (41.7%), Middle East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Therefore, the conference highlights will shed the light on the following main aspects: (1) etiology and genes, (2) treatment and impact, and (3) ongoing management, aiming to contribute to reducing the already recognized gaps in the treatment modalities/treatment pathway, treatment outcomes, mortality, and health care resource utilization in the Middle East, 2 especially with the increased number of diagnosed cases from the region 3 and the desire to raise the awareness on the recognition and modern management of X-linked hypophosphatemia (XLH). 4…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conference highlights will shed the light on the following main aspects: (1) etiology and genes, (2) treatment and impact, and (3) ongoing management, aiming to contribute to reducing the already recognized gaps in the treatment modalities/treatment pathway, treatment outcomes, mortality, and health care resource utilization in the Middle East, 2 especially with the increased number of diagnosed cases from the region 3 and the desire to raise the awareness on the recognition and modern management of X-linked hypophosphatemia (XLH). 4…”
Section: Introductionmentioning
confidence: 99%
“…X-linked hypophosphatemia (XLH) is one such rare bone condition. In the current issue of JDEP , Beshyah et al 2 undertook an online survey of clinicians in the Middle East and African countries to determine their knowledge of rare metabolic bone disorders and, more specifically, about XLH. While more than 80% of respondents were aware of XLH, the survey identified significant gaps in the clinicians' knowledge of symptoms of the condition and its management during the life course.…”
mentioning
confidence: 99%
“…The surveys by Beshyah et al 2 and Deeb et al 3 have identified the critical educational needs of teams of health professionals caring for patients with XLH and rare bone disorders. Two important questions arise from these surveys:…”
mentioning
confidence: 99%